THE IMPACT OF AGES CHANGING FIRM CHARACTERISTICS TOWARD STOCK RETURN IN INDONESIA - Edwin Wijaya; Sung Suk Kim (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This research was conducted to analyze whether the changes of the firm specific characteristics by aging have different effects on the stock performance in Indonesia. The firm specific characteristics we investigate are size, liquidity, momentum, systematic risk, market to book ratio, momentum, and profitability, and volatility. We use all the firms except financial industry from 2015 to 2019 in Indonesia Stock Market (IDX). The firm aging are divided into three groups, young, medium, and mature. Panel regression approach is applied to find the effects of the main variables. The results reveal that corporate aging does change the effects of the firm's characteristics on stock returns in Indonesia.